2022
DOI: 10.1177/02692163221103099
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate human resources, equipment and training: A qualitative assessment of the objectives of the NUHELP end-of-life care programme in the context of the COVID-19 pandemic

Abstract: Background: The COVID-19 pandemic had a particularly severe impact on nursing homes, exposing numerous pre-existing deficiencies in end-of-life care. Aim: To describe how the COVID-19 pandemic affected nursing home and primary care professionals’ attempts to achieve the objectives of a pre-existing end-of-life programme and to explore their personal experiences of end-of-life care in these facilities. Design: A qualitative descriptive study using thematic analysis. Setting/participants: Twenty semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In some cases, family members did not have the opportunity to say goodbye to the patient or had to say goodbye over the phone. This situation intensified the relationship between nurses and patients, as they did not have anyone else with them, resulted in the perception of patients dying alone, and professional healthcare workers consequently suffering burnout (Mota Romero et al, 2022). Both Montgomery et al (2021) and Wendlandt et al (2022) emphasize communication difficulties between healthcare staff and family members in the context of the COVID‐19 pandemic and the lack of understanding of family members about what was happening (Wendlandt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, family members did not have the opportunity to say goodbye to the patient or had to say goodbye over the phone. This situation intensified the relationship between nurses and patients, as they did not have anyone else with them, resulted in the perception of patients dying alone, and professional healthcare workers consequently suffering burnout (Mota Romero et al, 2022). Both Montgomery et al (2021) and Wendlandt et al (2022) emphasize communication difficulties between healthcare staff and family members in the context of the COVID‐19 pandemic and the lack of understanding of family members about what was happening (Wendlandt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of staff training and experience was another Determining factor of care, potentially worsened by the lack of protocols and the overall lack of knowledge at the time regarding COVID‐19 (Mota Romero et al, 2022; Puente‐Fernández et al, 2020). Inadequate numbers of trained staff to attend to the high number of patients requiring care in the first waves of the pandemic made it impossible to provide high‐quality care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strang et al [ 38 ] calculated that only 59% of those who died from COVID-19 were accompanied, either by professionals or family members. Despite the publication of regulations to prevent or limit the presence of relatives in nursing homes, the questionnaire responses indicated that these regulations were breached in order to facilitate the accompaniment of persons in their last days of life [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This question should be investigated further, given the need to ensure fluid collaboration between nursing homes and PHC workers and thus provide adequate end-of-life care. The multiple experiences of collaboration between professionals in both fields during the pandemic have brought positions closer in this regard, enabling PHC personnel to learn more about the work carried out in nursing homes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%